Modeling and Simulation of SVPWM Based Application - Ashish Porwal; Ketan Baria; Anuradha Deshpande (Institute of Advanced Engineering and Science, 2014)
Recent developments in power electronics and semiconductor technology have lead to widespread use of power electronic converters in the power electronic systems. A number of Pulse width modulation (PWM) schemes are used to obtain variable voltage and frequency supply from a three-phase voltage source inverter. Among the different PWM techniques proposed for voltage fed inverters, the sinusoidal PWM technique has been popularly accepted. But there is an increasing trend of using space vector PWM (SVPWM) because of their easier digital realization, reduced harmonics, reduced switching losses and better dc bus utilization. This project focuses on step by step development of SVPWM technique. Simulation results are obtained using MATLAB/Simulink software for effectiveness of the study.